Synthesis of Structured Triglycerides Based on Canarium Oil for Food Application - Johnner Sitompul; Tutus Gusdinar; Kusnandar Anggadiredja; Hamidah Rahman; Tursino Tursino (Journal of Engineering and Technological Sciences, 2018)
This paper concerns the synthesis of structured triglycerides containing different proportions and positions from medium- (M) and long-chain (L) fatty acids on a glycerol backbone. Structured triglycerides of MLM type were synthesized by utilizing canarium oil and incorporating caprylic acid (C8:0) as a source for the medium chain (M) fatty acids. Synthesis was performed through a two-step enzymatic reaction, with ethanolysis as the first step and esterification as the second step. Both reactions use the sn-1,3 specific lipase as a catalyst, which has specific activity at positions sn-1 and sn-3 of the triglyceride structure. The results from high-performance liquid chromatography showed that the stereospecific distribution of fatty acids in the structured triglyceride was 29.52±0.59 and 44.28±0.88 mol% of caprylic acid in the positions of sn-1,2,3 and sn-1,3, respectively. Furthermore, analysis of the physicochemical properties of both the native canarium oil and the structured triglycerides using an independent-sample t-test at p < 0.05 indicated that the two samples were significantly different for saponification number, iodium number, and average molecular weight. The results of this study showed that canarium oil can be exploited as a starting material for functional food application.